ChemInform Abstract: 5‐Membered Heterocycles with Directly‐Bonded Sandwich and Half‐Sandwich Termini as Multi‐Redox Systems: Synthesis, Reactivity, Electrochemistry, Structure and Bonding. Issue 45 (14th October 2013) - Hildebrandt, Alexander; Pfaff, Ulrike; Lang, Heinrich
Abstract Review: [synthesis, structure, bonding motif, reaction behavior, electrochem., spectroeectrochem.